Aerobic exercise ameliorates atherosclerosis-induced cognitive impairment via hippocampal IL-33/NF-κB signaling modulation - Peng, Jianwei; Chang, Zaoshang; Wang, Jinyun; Liao, Zijie; Yang, Yunjie; Mu, Lianwei; Wang, Shen; Huang, Junhao; Xia, Jingbo; Hu, Min (Frontiers in Physiology, 2025)
Atherosclerosis (AS), a common cardiovascular condition, is often linked to cognitive dysfunction. This study investigates how aerobic exercise affects cognitive impairments caused by AS in ApoE−/− mice. At 8 weeks old, male ApoE−/− mice were fed a high-fat, high-cholesterol diet (HFHCD) for 6 weeks to induce AS, with C57BL/6J mice on a standard diet as control group (WT). Initially, the study compared aortic plaque and cognitive performance between the WT and AS mice. Then, AS mice were divided into sedentary (AS-SED) and exercise (AS-EX) groups for a 10-week aerobic exercise intervention. Results showed significant aortic plaques and cognitive deficits in AS mice after 6 weeks on the HFHCD diet. However, the 10-week exercise reduced plaque, improved cognition, and enhanced cerebral blood flow. Exercise intervention also decreased IL-33 expression in the hippocampus and inhibited NF-κB and IκBα phosphorylation. Furthermore, aerobic exercise reduces M1 microglial activation and pro-inflammatory cytokines like IL-6, TNF-α, and IL-1β in the hippocampus of AS mice, thereby decreasing neuroinflammation. In summary, aerobic exercise can effectively improve cognitive function by decreasing IL-33 expression and inhibiting NF-κB activation, which in turn reduces microglial activation and the release of inflammatory mediators in the hippocampus. This study provides evidence for aerobic exercise to improve cognitive impairment caused by AS.